MODERN ADVANCEMENTS IN CERVICAL CANCER PREVENTION, EARLY RECOGNITION, AND PROGNOSTIC ASSESSMENT - Dildora B. Nasretdinova, (Central Asian Journal of Medicine, 2025)
This work highlights recent advancements in the field of cervical cancer, focusing on three critical areas: prevention, early detection, and prognostic evaluation. Emphasis is placed on the implementation of HPV vaccination programs, novel biomarkers, and molecular screening techniques that enhance early recognition of precancerous changes. Advances in imaging technologies and liquid-based cytology are also discussed as key tools for improving diagnostic accuracy. Furthermore, the study explores modern prognostic models, including genomic profiling and AI-based risk stratification, which aid in predicting disease progression and tailoring individualized treatment plans. Together, these innovations represent a significant step forward in reducing the incidence and mortality associated with cervical cancer.